Foundations of optimal control theory - Lee, E. B.; Markus, L. (New York: Wiley, 1967)
The mathematical theory of optimal control began about twenty years ago as a special topic within the discipline of differential equations. After the maximal principle and the method of dynamic programming were discovered, it was recognized that optimal control theory could be treated within the framework of the calculus of variations. However, many of the basic concepts of control theory still demanded an approach through the qualitative theory of differential systems, and it is from this viewpoint that this text has been prepared.
Bibliography: p. 537-568.
ne 22/03/2018
Loan
Keywords: Control theory